(untitled) (Raparin Journal of Humanities (RJH), 2020)
The research seeks to identify the factors child trafficking phenomenon and its consequences on the victims of child trafficking for work and begging which’s done by the Arabian refugee parents and relatives’ resident in camp and center of Sulaymaniyah governorate, According to human trafficking and labor law in Iraq. To collect the information a questioner has used which consist of 50 questions, and for analyzing information, Statistical Package for Social Science (SPSS) has used. The sample consists of 50 children, also Social Serviay method has used. According to the results of the research, there are many contributing factors behind this phenomenon; the major Factors are poverty, family tendency and or family pressure to doing it. According to the other outcome of the research, 62 percent of the sample of research confronted with violence, 58% of the sample dropped out from school or some of them illiterate and/or has arithmetic studding the total hour of working is more than nine hours.